(untitled) (British Journal of Global Ecology and Sustainable Development, 2026)
This study presents information on the effects of seed sowing rates and nitrogen fertilization on the grain quality indicators of chickpea varieties. The research focuses on the locally developed chickpea varieties "Obod" and "Polvon". The findings contribute to understanding how agronomic practices influence grain quality in these cultivars.